2020
DOI: 10.1002/ehf2.12913
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of heart failure due to giant coronary artery fistula: a case report

Abstract: Coronary artery fistula is a rare congenital cardiac anomaly that is often found incidentally during computed tomography angiography. Coronary fistula between the left circumflex coronary artery and the coronary sinus is among the less common forms of coronary artery fistula. A 60-yea\r-old female patient presented to our outpatient cardiology department with symptoms of severe, de novo heart failure. Echocardiogram revealed severe mitral regurgitation and a dilated duct that turbulently accelerated colour Dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Following transcatheter closure of the fistula, the patient displayed an improvement in symptoms but also experienced complications from a myocardial infarction. Similarly, Sandor et al [ 6 ] reported a patient with a fistula extending from the left circumflex coronary artery to the coronary sinus, along with a significant left-to-right shunt (Qp/Qs=2.159) and congestive heart failure. After undergoing fistula ligation, the patient was discharged with improved cardiac function.…”
Section: Discussionmentioning
confidence: 95%
“…Following transcatheter closure of the fistula, the patient displayed an improvement in symptoms but also experienced complications from a myocardial infarction. Similarly, Sandor et al [ 6 ] reported a patient with a fistula extending from the left circumflex coronary artery to the coronary sinus, along with a significant left-to-right shunt (Qp/Qs=2.159) and congestive heart failure. After undergoing fistula ligation, the patient was discharged with improved cardiac function.…”
Section: Discussionmentioning
confidence: 95%
“…Most coronary artery fistulae originate from the right coronary artery (40–60%) and mainly connect to the right atrium, right ventricle or pulmonary trunk [ 3 ] . Although it is a rare congenital or acquired entity, a CAF may present with different signs and symptoms depending on the number, size, location, haemodynamic profile and underlying comorbidities of the patient [ 1 , 3 , 4 ] . Clinical sequelae of CAFs may include dilatation of the heart chamber and dyspnoea, as well as ischaemia symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Transthoracic echocardiography showed dilated cardiomyopathy with severe depression transcatheter CAF closure demonstrate that this procedure is effective in most patients with suitable anatomy; however, it is not free of risks. The updated 2018 American College of Cardiology/American Heart Association guidelines recommend transcatheter closure or surgical closure for giant fistulas or when symptoms indicate obvious heart failure [4,5] . In our patient, given the coronary anatomy and large-calibre fistula, surgical intervention was suggested.…”
Section: Case Descriptionmentioning
confidence: 99%
“…A CCF that drains to the left ventricle (LV) produces hemodynamic changes similar to those of aortic regurgitation, and a CCF that drains to the left atrium (LA) results in volume overload similar to that of mitral regurgitation [6]. If left untreated, CCFs may result in clinical complications, such as myocardial ischemia [7], ventricular dysfunction [8], aneurysmal formation [9], and infective endocarditis [10].…”
Section: Introductionmentioning
confidence: 99%